Comprehensive Review of Lymphatic Filariasis: Recent Advances in Pathogenesis, Diagnostic Methods, and Modern Therapeutic Strategies - Al-Tikrity, Dunia Abed Hussein; Abdullah, Hanan Adhawi (Journal of Science in Medicine and Life, 2025)
The review investigates lymphatic filariasis (LF) through an analysis of pathogenesis together with tests for diagnosis and available treatment approaches. The research demonstrates the complicated pathophysiological relationship between disease agents especially focusing on Wolbachia bacteria as well as difficulties in diagnosing covert infections. The author recommends implementing FNAC testing to detect LF during the early stages particularly for patients without symptoms. The review demonstrates antibiotic treatment of Wolbachia bacteria as a powerful intervention for both medical care and worldwide disease management.